Využití simulačních metod v procesu oceňování podniku - Tesař, Jan (2025)
This master's thesis focuses on the analysis and application of simulation methods in the business valuation process. The main objective of this thesis is to implement the Semi-Investment valuation theory based on imperfect capital markets assumptions, point out their strengths, shortcomings and provide a practical guidance. This method relies on utilization of simulation methods in business valuation process by selecting the appropriate probability distribution based on means of risk analysis and asses the company specific aggregated risk, measured by appropriate risk measures. Furthermore, simulation methods are implemented into the traditional valuation framework relying on CAPM, potentially enhancing the accuracy and provide a valuable probabilistic view on the value of the firm.